2019
DOI: 10.1029/2018gb005967
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Degradative Loss of Terrigenous Organic Carbon in Surface Sediments Across the Laptev and East Siberian Sea

Abstract: Ongoing permafrost thaw in the Arctic may remobilize large amounts of old organic matter. Upon transport to the Siberian shelf seas, this material may be degraded and released to the atmosphere, exported off‐shelf, or buried in the sediments. While our understanding of the fate of permafrost‐derived organic matter in shelf waters is improving, poor constraints remain regarding degradation in sediments. Here we use an extensive data set of organic carbon concentrations and isotopes ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 79 publications
5
27
0
Order By: Relevance
“…However, Bröder et al (2019) reported on slow C degradation rates of terrestrial C in the top layer of seafloor sediments, of which a majority was considered even resistant to degradation. In addition, a large amount of the permafrost C might become re-buried in marine sediments of the Laptev and East Siberian Sea shelf (Vonk et al, 2012;Vonk and Gustafsson, 2013;Bröder et al, 2019).…”
Section: Fate Of Eroded Organic Matter and Implications For The Ecosymentioning
confidence: 99%
See 1 more Smart Citation
“…However, Bröder et al (2019) reported on slow C degradation rates of terrestrial C in the top layer of seafloor sediments, of which a majority was considered even resistant to degradation. In addition, a large amount of the permafrost C might become re-buried in marine sediments of the Laptev and East Siberian Sea shelf (Vonk et al, 2012;Vonk and Gustafsson, 2013;Bröder et al, 2019).…”
Section: Fate Of Eroded Organic Matter and Implications For The Ecosymentioning
confidence: 99%
“…The deep mobilization of permafrost C caused by thermo-erosional processes along shores might add C to the atmosphere, which is not yet taken into account in current Earth System Models that include only topdown thaw (Turetsky et al, 2020). However, how much of the C released through shore erosion is re-buried on the Arctic shelf or in the deep Arctic Ocean versus is being mineralized and released into the atmosphere is still a matter of discussion (Vonk et al, 2012;Bröder et al, 2019;Grotheer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In offshore resuspension areas with very high TSM concentration, DOC and TSM do not necessarily co-vary. Large amounts of terrigenous organic matter can be mineralized on short timescales (about 50 % within a year; Kaiser et al, 2017) and strongly degraded when deposited in sediments (Bröder et al, 2016(Bröder et al, , 2019Brüchert et al, 2018).…”
Section: Ocrs Algorithms In Shallow Arctic Fluvial-marine Transition mentioning
confidence: 99%
“…Huge amounts of soil organic carbon are currently stored frozen in permafrost soils (e.g., Tarnocai et al, 2009;Zimov et al, 2009), and vast amounts of methane, in a solid form as gas hydrates, are trapped in permafrost and at shallow depths in cold ocean sediments (e.g., Romanovskii et al, 2005). With increasing temperature of the permafrost (Romanovsky et al, 2010) and the water at the seafloor, as a result of increased surface warming in Arctic regions (Stocker et al, 2013), a widespread increase in the thickness of the thawed layer and the decomposition of hydrates could lead to the release of large quantities of CH 4 (and CO 2 ) to the atmosphere (ACIA, 2004(ACIA, , 2005Anisimov et al, 1997;Goulden et al, 1998;Michaelson et al, 1996) as well as an enhanced mobilization and export of old, previously frozen soil-derived organic carbon (e.g., Bröder et al, 2018;Bröder et al, 2019;Schuur et al, 2008;Tesi et al, 2016;Vonk et al, 2012;Winterfeld et al, 2015Winterfeld et al, , 2018. The release of these greenhouse gases in turn would create a positive feedback mechanism that can amplify regional and global warming.…”
Section: Permafrostmentioning
confidence: 99%